RETRACTED: Study of thermal characteristics of energy efficient micro channel heat sinks in advanced geometry structures and configurations: A review - Rehman, Zabdur; Ahmad, Faraz; Muhammad, Hafiz Ali; Riaz, Fahid; Ayub, Hafiz Muhammad Uzair; Hasan, Mudassir; Lee, Moonyong (Frontiers in Energy Research, 2022)
The sustainability and economic development is intertwined with the energy consumption and conversion processes. To suffice the ever-increasing demand of energy consumption amid environmental concerns, energy conservation and recovery along with the harnessing of renewable energy has been mandated by the policy regulators. In any energy conversion process, heat exchangers are vital operation component and has been part of any energy conversion process since the NINETIETH century. However, due to the increased energy demand, requirement of high efficiency and space and material constraints, the need for miniaturized light-weight heat exchangers with adequate heat transfer characteristics persists. Traditional heat exchanger use tubes of 6mm (dm or radius) with different cross sectional areas, orientation and surface textures but the traditional technology has been saturated. The miniaturized micro channel heat exchangers with tubes of about 1mm have a tremendous potential to further enhance the heat transfer performance. They offer superior heat transmission, are light weight and saves space and material . MCHS is relatively new concept and the literature lacks in their systematic design methodology and design correlations. The researchers are investigating the validity of conventional heat exchanger correlations for the design of MCHS. This study examines the existing literature on the MCHS’s, their potential and discuss the challenges associated with the design and development of MCHSs.